Crystal structure of 3-{5-[(2-chlorophenyl)carbonyl]-2-oxo-1,3- benzothiazol-3(2H)-yl}propanoic acid, C17H12ClNO4S - Aydin, Abdullah; Akkurt, Mehmet; Onkol, Tijen; Büyükgüngör, Orhan (Walter de Gruyter GmbH, 2010)
C17H12ClNO4S, monoclinic, P12(1)/c1 (no. 14), a = 13.1203(8) angstrom, b = 16.6201(9) angstrom, c = 7.7539(4) angstrom, beta = 103.559(5)degrees, V = 1643.7 angstrom(3), Z = 4, R-gt(F) = 0.046, wR(ref)(F-2) = 0.131, T = 296 K.
Keywords: Crystallography; QD901-999; Physics; QC1-999